Tremella rhizocarpicola sp. nov. and other interesting lichenicolous Tremellales and Filobasidiales in the Nordic countries - Millanes, Ana; Diederich, Paul; Westberg, Martin; Knutsson, Tommy; Wedin, Mats (MycoKeys, 2014)
New data on the diversity and geographical distribution of lichenicolous Tremellales and Filobasidiales in the Nordic countries is presented. One new species, Tremella rhizocarpicola, is formally described. Tremella pertusariae and T. protoparmeliae are reported as new to the Nordic countries, Syzygospora physciacearum is new to Iceland, Tremella rinodinae is new to Sweden, and T. caloplacae is new to Norway. Nine species are reported as new to a number of Swedish provinces, including Biatoropsis usnearum, Syzygospora bachmannii, S. physciacearum, Tremella caloplacae, T. cetrariicola, T. cladoniae, T. coppinsii, T. diploschistina, and T. hypogymniae.